Enantioselective Construction of Silicon‐Stereogenic Silanes by Scandium‐Catalyzed Intermolecular Alkene Hydrosilylation - Zhan, Gu; Teng, Huai‐Long; Luo, Yong; Lou, Shao‐Jie; Nishiura, Masayoshi; Hou, Zhaomin (Angewandte Chemie International Edition, 2018)
The catalytic asymmetric construction of silicon‐stereogenic silanes is of great interest and significance, but has met with only limited success to date. We herein report the enantioselective hydrosilylation of alkenes with dihydrosilanes by a chiral half‐sandwich scandium catalyst, which constitutes an efficient and general route for the synthesis of a wide range of enantioenriched silicon‐stereogenic silanes from easily accessible starting materials. This reaction features a broad substrate scope, high yields, and high enantioselectivity. Some of the chiral tertiary silane products were also converted into valuable derivatives, such as chiral silanol, quaternary silane, and benzosilole compounds. A chiral half‐sandwich scandium catalyst enables the highly enantioselective hydrosilylation of alkenes with dihydrosilanes. This process constitutes an efficient and general route for the synthesis of a wide range of enantioenriched silicon‐stereogenic silanes from easily accessible starting materials.